2012
DOI: 10.1890/es11-00343.1
|View full text |Cite
|
Sign up to set email alerts
|

A feather‐precipitation hydrogen isoscape model for New Zealand: implications for eco‐forensics

Abstract: H p ) isoscape. We used feathers from two non-migratory bird species that are widely distributed around New Zealand, Tui (Prosthemadera novaeseelandiae) and California Quail (Callipepla californica). Feathers were sampled from archived birds that were collected between 1880 and 2006 obtained from three New Zealand museum collections located at Auckland, Wellington and Christchurch. Forensic isotopic assays of feather from known locations were compared with the precipitation isoscape model with the aim of estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…The regression model reported by Rogers et al [14] was shown to be significant with r 2 = 0.86 and model parameter estimates were significant at p < α = 0.01. The determined precipitation isoscape was then linked to δ 2 H values measured from historic feathers from known locations by simple linear regression (r 2 = 0.48) and utilised to investigate the potential geographic origins of feathers from historic Maori cloaks [14].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…The regression model reported by Rogers et al [14] was shown to be significant with r 2 = 0.86 and model parameter estimates were significant at p < α = 0.01. The determined precipitation isoscape was then linked to δ 2 H values measured from historic feathers from known locations by simple linear regression (r 2 = 0.48) and utilised to investigate the potential geographic origins of feathers from historic Maori cloaks [14].…”
Section: Introductionmentioning
confidence: 85%
“…The data obtained through the CDRP project have since been utilised to determine local precipitation isoscapes across New Zealand. Rogers et al [14] reported an initial mean annual precipitation δ 2 H isoscape which was calculated using a multiple linear regression (MLR) approach based on elevation, mean annual temperature, and mean annual precipitation. The regression model reported by Rogers et al [14] was shown to be significant with r 2 = 0.86 and model parameter estimates were significant at p < α = 0.01.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although potential regional isotopic variation could introduce uncertainty, we believe it should be negligible given that eastern Canada and new england are geographically proximate and that Kays and Feranec (2011) found relatively good separation in isotopic values between wild and captive canid diets. We categorized new Brunswick and Quebec wolves as "wild" or "captive" using an assignment test based on likelihood analysis (Rogers et al 2012). From each measured wolf δ 13 C value, we depicted the likely origin of individuals and summarized the likelihood of origin for each wolf based on the average probability across our replicate samples.…”
Section: Stable Isotope Analysesmentioning
confidence: 99%